Studying luxury - Olivier Dehoorne; Sopheap Theng (Études Caribéennes)
This paper proposes to study luxury through a multidisciplinary approach, from philosophy to sociology and from psychology to economy. First of all, it is essential to identify the foundations of luxury, with the work of Veblen (conspicuous consumption), Bourdieu (distinction and habitus) and Lipovetsky (aesthetisation), and to define the contours of luxury. Luxury is part of a historical construction. It is associated with “perfection” (Karpik). Refinement, inner quest, distinction, pleasure of creativity and innovation, luxury is a combination of tangible and intangible composite. On the economic front, luxury is the economics of singularities (Karpik). The price is the main measurable indicator that helps to distinguish the luxury market.